1995
DOI: 10.1074/jbc.270.31.18295
|View full text |Cite
|
Sign up to set email alerts
|

A String of Enzymes, Purification and Characterization of a Fusion Protein Comprising the Four Subunits of the Glucose Phosphotransferase System of Escherichia coli

Abstract: A multidomain protein comprising the four subunits of the glucose phosphotransferase system of Escherichia coli was constructed by fusion of the transmembrane subunit IICBGlc and the three cytoplasmic proteins, IIAGlc, HPr, and enzyme I. The subunits were linked in the above order with Ala-Pro-rich linkers; the fusion protein was overexpressed in E. coli and purified by Ni2+ chelate affinity chromatography. Approximately 3 mg of the fusion protein could be purified from 1 liter of culture. The phosphotransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Protein Purification and Activity assay-The Dha kinase of C. freundii was overexpressed in E. coli K12 WA2127⌬ HIC (⌬ manXYZ ⌬ ptsHIcrr) (36). Cells (3 liters) were grown at 37°C and induced with 200 M isopropyl-1-thio-␤-D-galactopyranoside at A 600 ϭ 0.8, and incubation continued for 5 h. Cells were collected by centrifugation, and the sediment was resuspended in buffer A (25 ml, 50 mM NaP i , pH 8.0, 10 mM ␤-mercaptoethanol, 500 mM NaCl), broken by two passages in a French pressure cell, and fractionated by differential centrifugation into cell debris (10 min, 3000 ϫ g), membrane fraction (60 min, 150,000 ϫ g), and cytoplasmic fraction (supernatant), which was mixed with 10 ml of Ni 2ϩ -nitrilotriacetic acid resin (Qiagen) and allowed to adsorb for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Protein Purification and Activity assay-The Dha kinase of C. freundii was overexpressed in E. coli K12 WA2127⌬ HIC (⌬ manXYZ ⌬ ptsHIcrr) (36). Cells (3 liters) were grown at 37°C and induced with 200 M isopropyl-1-thio-␤-D-galactopyranoside at A 600 ϭ 0.8, and incubation continued for 5 h. Cells were collected by centrifugation, and the sediment was resuspended in buffer A (25 ml, 50 mM NaP i , pH 8.0, 10 mM ␤-mercaptoethanol, 500 mM NaCl), broken by two passages in a French pressure cell, and fractionated by differential centrifugation into cell debris (10 min, 3000 ϫ g), membrane fraction (60 min, 150,000 ϫ g), and cytoplasmic fraction (supernatant), which was mixed with 10 ml of Ni 2ϩ -nitrilotriacetic acid resin (Qiagen) and allowed to adsorb for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For ␣ϭ 1, crowding effects are assumed to be absent. Mao et al (28) reported the isolation, purification and reconstitution of a fusion protein comprising the four glucose PTS enzymes of E. coli, in which the different enzymes were joined by flexible linkers. In agreement with our results, the phosphorylation activity of an equimolar mixture of the individual isolated enzymes varied more than linearly but less than quadratically with the total enzyme concentration (figure 2A in ref.…”
Section: Figmentioning
confidence: 99%
“…From our studies, the gene organization of the glucose permeases in Gram-positive bacteria did not correlate with a specific phylogenetic branch, but instead seemed to be more related to the ecological niches of the bacteria. In vitro analyses of the E. coli glucose PTS showed that a fusion protein made of IIC Glc , IIB Glc and IIA Glc domains linked together exhibited higher phosphotransferase activity than a mixture of the isolated subunits (Mao et al, 1995). These data suggested that the linking of functional domains could be an advantage regarding the activity of the permease.…”
Section: Discussionmentioning
confidence: 66%